The Nasal-associated Lymphoid Tissue of Adult Mice Acts as an Entry Site for the Mouse Mammary Tumor Retrovirus - Velin, Dominique (The Rockefeller University Press, 1997)
Mouse mammary tumor virus (MMTV) is a B type retrovirus transmitted to the suckling offspring through milk. MMTV crosses the intestinal barrier of neonates, initially infects the lymphoid cells of the Peyer's patches, and later spreads to all lymphoid organs and to the mammary gland. Adult mice can be infected systemically, but not by oral MMTV administration. In this study, we show that nasal administration of infected milk induces the infection of adult mice. Nasal MMTV infection shared the main features of systemic and neonatal intestinal MMTV infections: deletion of the superantigen (SAg)-reactive T cell subset from the peripheral T cell population, presence of viral DNA in lymphoid cells, and transmission of MMTV from mother to offspring. Viral DNA was restricted to the lungs and nasal-associated lymphoid tissue (NALT) 6 d after nasal infection. Furthermore, SAg-induced T cell proliferation was only detected in NALT. These results demonstrate that MMTV crosses the intact epithelium of the upper respiratory tract of adult mice and infects the lymphoid follicles associated with these structures.